Reimagining Catholicity: An Interstitial Perspective - Joseph, Jaisy A. (Asian Horizons, 2020)
University/Institution: Boston College (USA) Faculty/Department: Theology Director of the Doctoral Dissertation: Dr Richard R. Gaillardetz Year of Doctoral Defence: 2019